Penilaian Pengetahuan, Sikap, Dan Praktik Pelaku Industri Pariwisata Terhadap Covid-19 Di Labuan Bajo - Hutagalung, Septian; Rudiyanto, Roseven (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i02.p13, 2021)
Cases of pneumonia caused by the novel corona virus or 2019-nCoV, known as COVID-19 have spread throughout the world. One of the industries affected by the massive spread of the disease is tourism. This happens because human movement is restricted. West Manggarai Regency, which has Labuan Bajo as a priority tourism destination in Indonesia, is experiencing a loss of local revenue (PAD). Moreover, tourism is the largest passenger of PAD in West Manggarai Regency. In response to the impact of tourism, the government reopened Komodo National Park. A quantitative approach to data collection through surveys is the method used in this study. The sampling technique used in this study was purposive sampling technique, where the individuals who were the respondents had certain criteria according to the research needs, such as age and the field of tourism where they worked. There is a measuring tool in this study adapted from a study of the knowledge, attitudes and practices (PSP) of the Malaysian population against COVID-19 in Malaysia and China. Therefore, researchers consider it necessary to study the knowledge, attitudes and practices of tourism industry players towards COVID-19 as a basis for assessing the readiness of industry players to open the flow of tourists to Labuan Bajo during the COVID-19 pandemic. The results of this study show that tourism industry players in Labuan Bajo have low knowledge scores about COVID-19, an optimistic attitude that the COVID-19 pandemic will be controlled, and in practice tourism industry players use masks and wash their hands with soap or hand. sanitizer in everyday life, but still visit crowded places even though it's not urgent.